Socio-interactionist approach in the practice of teachers of the municipal public network of the Great Island of São Luís - MA - Santos, Marcos Antônio Fernandes dos (2023)
The psychology of learning has contributed greatly for teachers to resign their practices, based on assumptions that clarify the different ways of teaching and learning, which reflects in the improvement of the quality of education offered by schools. Among these assumptions, for example, we highlight that of the theoretician Vygotsky (1989), who postulated about human development and the learning process from the interaction of the subject with the medium of which he is part. Its theoretical aspect became known, then, as sociointeractionism. In this sense, this article aimed to investigate the contributions of the socio-interactionist approach in the practice of teachers of the municipal network of the Greater Island of São Luís, in the state of Maranhão. The proposal of this research has a qualitative character, as to the type of research, which is still descriptive, regarding the objectives. Field research was also carried out, in which the participating public were ten teachers of basic education in Maranhão. The data collection instrument, therefore, was a questionnaire with five open questions. Thus, the results revealed that teachers have basic knowledge about the approach proposed by Vygotsky and develop practices involving socio-interactionist methodologies, although they realize that it is still necessary that this perspective is more explored by teachers and educational institutions, including those of which they are part.